COMPLIANCE OF NURSES TO NATIONAL CORE COMPETENCY STANDARDS - Martinez, Cecilia O (LIFE: International Journal of Health and Life-Sciences, 2017)
This study was conducted to determine the compliance of 446 staff nurses to National Core Competency Standards. Based on the results, generally the staff nurses were Nurse 3 assigned at the General Wards, mostly from Hospital D and with work experience of 1 to 3 years; the respondents and their supervisors gave a rating of very high level of compliance in Patient Care, Empowering, Enhancing and Enabling Competencies; When grouped according to work position, there was a significant difference on the level of compliance in terms the competency: Patient Care – Communication, Enhancing and Enabling; in terms of unit of practice / department, there was a significant difference on the level of compliance in terms Enabling Competency; in terms of length of work experience as nurse practitioner, there were no significant difference in any of the 4 Competency Standards; in terms of hospital assigned; there was a significant difference in terms of the competencies: Patient Care, Enhancing and Enabling; lastly, there was a significant differences in the evaluation of the staff nurses and their supervisors in terms of the competencies: Patient Care – Safe and Quality Nursing Care, Empowering, Enhancing and Enabling; The problems encountered by staff nurses in complying were time constraints, work overload, communication barriers and lack of feedback.It is recommended that staff nurses should continue to become familiar and updated with the Core Competency Standards. Further analysis of their compliance to competency standards should be done for the basis of planning relevant and targeted educational programs and interventions to enhance nurses’ professional competence. With regards to the patients, they should be educated about being active partners in the provision of care through accurate reporting of data and assessment feedback, so that staff nurses will be aware as to how to comply with the care they need.